2016
DOI: 10.1007/s13238-016-0272-7
|View full text |Cite
|
Sign up to set email alerts
|

MiR-130a regulates neurite outgrowth and dendritic spine density by targeting MeCP2

Abstract: MicroRNAs (miRNAs) are critical for both development and function of the central nervous system. Significant evidence suggests that abnormal expression of miRNAs is associated with neurodevelopmental disorders. MeCP2 protein is an epigenetic regulator repressing or activating gene transcription by binding to methylated DNA. Both loss-of-function and gain-of-function mutations in the MECP2 gene lead to neurodevelopmental disorders such as Rett syndrome, autism and MECP2 duplication syndrome. In this study, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…In this study, we present evidence that cytoskeletal disruption also contributes to neurodegeneration in the ENS during early stages of PD; miR-130a-3p expression was upregulated in psA30P mice. This miRNA inhibits neurite outgrowth and reduces dendritic spine density 74 . It also targets MECP2, which induces symptoms in patients with Rett syndrome that are similar to those seen in PD and dopamine metabolism disorders 75 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we present evidence that cytoskeletal disruption also contributes to neurodegeneration in the ENS during early stages of PD; miR-130a-3p expression was upregulated in psA30P mice. This miRNA inhibits neurite outgrowth and reduces dendritic spine density 74 . It also targets MECP2, which induces symptoms in patients with Rett syndrome that are similar to those seen in PD and dopamine metabolism disorders 75 .…”
Section: Discussionmentioning
confidence: 99%
“…miR-130a is an anti-angiogenic transcription factor. The study of Jiang et al (15) showed that the expression of miR-130a is positively proportional to the cerebral water content in rats with cerebral edema, suggesting that miR-130a may be associated with the formation of cerebral edema (16). Furthermore, Altintas et al (17) found that miR-130a also plays an important regulatory role in diabetic rats with transient CI.…”
Section: Discussionmentioning
confidence: 99%
“…These GO categories and KEGG pathways are closely related to the proliferation and differentiation of NSCs. Studies have shown that miR-106b could promote the renewal of NSCs and inhibit their differentiation 29 ; miR-130a and miR-138 could inhibit axon growth and regeneration 30 , 31 ; miR-20b overexpression could downregulate the expressions of Map2 and Tubb3 (well-known neuronal markers) 32 . In this study, we observed that these miRNAs were upregulated in the early stage of NSCs after miR-31 overexpression.…”
Section: Discussionmentioning
confidence: 99%